Antoine Compagnon, "Demon teorije", prijevod: Morana Čale, AGM, Zagreb, 2007. - Majić, Ivan, kroatist (Array, 2009)
Rad je kritički prikaz knjige "Demon teorije" Antoinea Compagnona, AGM, Zagreb, 2007.